Respostas

A melhor resposta!
2014-06-01T14:19:05-03:00
Fácil, só fatorar.

1)
a)
(x + 3)² = 
x² + 6x + 9

b)
(x-3)² = 
x² - 6x + 9

c)
(2x + 3)² =
4x² + 12x + 9

d)
(x+4)(x-4) =
x² - 16

e)
(3x² + 2)² =
9x^4 + 12x² + 4

f)
(x² + 2)(x² - 2)
x^4 - 4

2)
a)
4x +8 =
4(x + 2)

b)
x² + 3x =
x( x +3)

c)
3x³ + 6x² =
x² (3x + 6)

d)
x² - 16 =
(x - 4)(x + 4)

e)
16 - x² =
(4 - x)(4 + x)

f)
9x² - 25 =
(3x - 5) ( 3x + 5)

g)
5x + ax + 5y + ay
5(x + y) + a( x + y)
(5 + a) ( x + y)

h)
x³ + 2x² + 7x + 14
7(x + 2) + x²( x + 2)
(x +2) ( 7 + x²)

3)
a)
(-3)² = 9

b)
5³ = 125

c) 
(-1)^8 = 1

d)
(3/4)² = 9/16

e)
(-3/4)³ = -27/64

f)
(2²)³ = 2^6 = 64

4) ?????

5)
3x - 5  
3 * (4) - 5
12 - 5
7
1 5 1